Re: Solution
- To: mathgroup at smc.vnet.net
- Subject: [mg9873] Re: Solution
- From: Michaela Meier <michaela.j.meier at rz.ruhr-uni-bochum.de>
- Date: Sat, 29 Nov 1997 00:11:01 -0500
- Organization: Ruhr-Uni-Bochum
- References: <65m6hg$ab3@smc.vnet.net>
- Sender: owner-wri-mathgroup at wolfram.com
Awwad A. Al-Harthi wrote: > > Does anyone know how to solve for R from the equation > > R = ( G * e^ln(R + G/G)) - G Hi, This is what I learned in school :-) R = ( G * e^ln(R + G/G)) - G R = ( G * e^ln(R + 1)) - G R = ( G * (R + 1)) - G R = ( G * R +G) - G R = G*R R * (1 - G) = 0 So the solution would be R = 0 or G = 1 Michaela